2020
DOI: 10.1002/term.2994
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic stimuli and rotating suspension culture enhance conversion of human adipogenic mesenchymal stem cells into highly conductive cardiac progenitors

Abstract: Clinical trials using human adipogenic mesenchymal stem cells (hAdMSCs) for the treatment of cardiac diseases have shown improvement in cardiac function and were proven safe. However, hAdMSCs do not convert efficiently into cardiomyocytes (CMs) or vasculature. Thus, reprogramming hAdMSCs into myocyte progenitors may fare better in future investigations. To reprogramme hAdMSCs into electrically conductive cardiac progenitor cells, we pioneered a three‐step reprogramming strategy that uses proven MESP1/ETS2 tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Forskolin and Rolipram have been used in numerous protocols of cell reprogramming and differentiation, and have been reported as “reprogramming facilitators” since they have been shown to promote cell fate plasticity ( Qin et al., 2017 ; Ma et al., 2017 ). Moreover, previous data from our lab (data not shown) suggested that the treatment of cardiac progenitor cells with Epinephrine resulted in the differentiation of the progenitor cells into cardiac conduction-like cells via the transcription activation of key CCS channel proteins including SCN5a ( Islas et al., 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“…Forskolin and Rolipram have been used in numerous protocols of cell reprogramming and differentiation, and have been reported as “reprogramming facilitators” since they have been shown to promote cell fate plasticity ( Qin et al., 2017 ; Ma et al., 2017 ). Moreover, previous data from our lab (data not shown) suggested that the treatment of cardiac progenitor cells with Epinephrine resulted in the differentiation of the progenitor cells into cardiac conduction-like cells via the transcription activation of key CCS channel proteins including SCN5a ( Islas et al., 2020 ).…”
Section: Discussionmentioning
confidence: 76%
“… 37 , 38 In MSCT, ETS genes have been reported as targets for the protection and regeneration of cardiac muscle and bone matrix by MSCs or their exosomes. 39 , 40 Therefore, we tested ETS2 expression, and the results of the luciferase and ChIP assays indicated that ETS2 expression was decreased in ERK1 −/− BMMSCs, suggesting that ETS2, especially the ETS2-2- and ETS2-3-predicted binding sites on the aurka promoter region, transfers the signal from ERK1 to AURKA. Combining all the evidence, we demonstrated that ERK1, but not ERK2, induced T cell apoptosis via the ETS2/AURKA/NF-κB/Fas cascade.…”
Section: Discussionmentioning
confidence: 99%
“…One clear advantage of these materials is their help in promoting electrical conductivity, particularly in differentiating cells and other stimulants. Certain maturation properties are achieved, such as the induction of Purkinje-like cells [ 93 , 108 , 109 ]. Fibrin is a naturally occurring biomaterial, a biopolymer formed during coagulation [ 98 , 110 ].…”
Section: Materials Used For Artificial Scaffold Constructionmentioning
confidence: 99%